Condensação de Knoevenagel e síntese de n-acilidrazonas catalisadas por nanopartículas magnéticas funcionalizadas - Resende Filho, João Batista Moura de (2016)
The Knoevenagel condensation is one of the most important methods to perform new C-C bonds in organic compounds, and it was used at least in one-step on the synthesis of several molecules. The N-acylhydrazones, in turn, are molecules with considerable biological activity, which increased the number of papers involving the synthesis of N-acylhydrazones in the last years. This present work consists of the use of magnetic nanoparticles functionalized as catalysts in the Knoevenagel condensations and the synthesis of N-acylhydrazones. The magnetic nanoparticles, Fe3O4, were prepared by the chemical co-precipitation method, coated with sílica, Fe3O4@SiO2, and functionalized with amino groups (Fe3O4@SiO2-3N, which 3N = N1-(3-trimethoxysilylpropyl)diethylenetriamine) and lanthanide ions (Fe3O4@SiO2-1N-EDTA-Tb3+, which 1N = (3-aminopropyl)trimethoxysilane). These materials were characterized by absorption spectroscopy in infrared region, X-ray diffraction (X-RD), thermogravimetric analysis, elemental analysis of carbon, hydrogen and nitrogen, and magnetization measurements. The Fe3O4@SiO2-3N magnetic nanoparticles were used as catalysts in the Knoevenagel condensation, showing good isolated yields (71-100%) and reaction times (10-45 min). The amino groups in the functionalized magnetic nanoparticle act as bases, promoting the desprotonation of methylene group, and as catalyst in the reaction, activating the carbonylic carbon by the iminium ion formation. The Fe3O4@SiO2-1N-EDTA-Tb3+ magnetic nanoparticles were used as catalysts in the synthesis of N-acylhydrazones, showing also good isolated yields (65-95%) and reaction times (2-180 min). In conclusion, the magnetic nanoparticles synthetized showed a good catalytic activity, easilly recovered by magnetic separation and reused in subsequent reactions.